Syndicated Financing at Bank Syariah Indonesia in the Perspective of Sharia Economic Law - Muqsith, Muhammad; Herdiana Abdurrahman, Nana; Prasetyo, Yoyok (Zona Law And Public Administration Indonesia, 2024)
The purpose of this article is to describe and analyze syndicated financing of Islamic banks in Indonesia from the point of view of sharia economic law. This research uses qualitative research methods with the type of literature research used to analyze the formulation of this research problem. The results of this study show that Islamic banking product innovation can be achieved through the introduction of hybrid contracts or multiple contracts. Syndicated financing products emerged in the banking world due to the need for large amounts of financing, which Islamic banks could not support alone. Therefore, it must cooperate with other banks. Syndicated financing is allowed based on Fatwa DSN Number 91/DSN-MUI/IV/2014. Sharia syndicated financing at Islamic banks usually uses the Musharakah Mutanakisha contract.